Natural Killer Cells: The Linchpin for Successful Cancer Immunotherapy - Shaver, Kari A.; Croom-Perez, Tayler J.; Copik, Alicja J. (Frontiers in Immunology, 2021)
Cancer immunotherapy is a highly successful and rapidly evolving treatment modality that works by augmenting the body’s own immune system. While various immune stimulation strategies such as PD-1/PD-L1 or CTLA-4 checkpoint blockade result in robust responses, even in patients with advanced cancers, the overall response rate is low. While immune checkpoint inhibitors are known to enhance cytotoxic T cells’ antitumor response, current evidence suggests that immune responses independent of cytotoxic T cells, such as Natural Killer (NK) cells, play crucial role in the efficacy of immunotherapeutic interventions. NK cells hold a distinct role in potentiating the innate immune response and activating the adaptive immune system. This review highlights the importance of the early actions of the NK cell response and the pivotal role NK cells hold in priming the immune system and setting the stage for successful response to cancer immunotherapy. Yet, in many patients the NK cell compartment is compromised thus lowering the chances of successful outcomes of many immunotherapies. An overview of mechanisms that can drive NK cell dysfunction and hinder immunotherapy success is provided. Rather than relying on the likely dysfunctional endogenous NK cells to work with immunotherapies, adoptive allogeneic NK cell therapies provide a viable solution to increase response to immunotherapies. This review highlights the advances made in development of NK cell therapeutics for clinical application with evidence supporting their combinatorial application with other immune-oncology approaches to improve outcomes of immunotherapies.